Clinical and Microbiological Characterization of Invasive Pulmonary Aspergillosis Caused by Aspergillus lentulus in China - Yu, Shu-Ying; Guo, Li-Na; Xiao, Meng; Zhou, Meng-Lan; Yuan, Ying; Wang, Yao; Zhang, Li; Sun, Tian-Shu; Ning, Ya-Ting; Jia, Pei-Yao; Kang, Wei; Kong, Fanrong; et al. (Frontiers in Microbiology, 2020)
Invasive Aspergillosis (IA) due to Aspergillus lentulus is associated with high mortality. In this study, we investigated the clinical and microbiological characteristics of 6 fatal cases of proven or probable IA caused by A. lentulus in China. Underlying immunosuppression, prior antifungal exposure and intensive care unit (ICU) hospitalization were significant risk factors for invasive A. lentulus infection. Phenotypic differences were observed for A. lentulus isolates including slower growth, reduced sporulation and inability to grow at 48°C, compared with Aspergillus fumigatus complex. ITS sequencing was unable to distinguish A. lentulus from A. fumigatus, but sequencing of the benA, CaM and rod A loci enabled reliable distinction of these closely-related species. Phylogenetic analysis further confirmed that the ITS region had little variation within the Aspergillus section Fumigati whilst the benA gene offered the highest intraspecific discrimination. Microsatellite typing results revealed that only loci on chromosomes 1, 3, 5 and 6b generated detectable amplicons for identification. All A. lentulus isolates showed in vitro resistance to multiple antifungal drugs including amphotericin B (MIC range 4 to 8 μg/ml), itraconazole (MIC 2 μg/ml), voriconazole (MIC of 8~16 μg/ml) and posaconazole (MIC of 0.5~1 μg/ml). However, MECs for the echinocandin drugs, ranged from 0.03~0.25, ≤0.08~0.15 and ≤0.08 μg/ml for caspofungin, micafungin and anidulafungin, respectively. A. lentulus is an emerging fungal pathogen in China, causing fatal disease and clinicians as well as laboratories should be alert to their increasing presence